2009
DOI: 10.1007/s00436-009-1597-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of memory responses following Plasmodium chabaudi AS infection in mice distinct in susceptibility to clinical malaria

Abstract: Plasmodium chabaudi chabaudi AS blood stage infection results in various degrees of clinical symptoms to malaria depending on the mouse strain. This study aimed to investigate the development of memory responses in susceptible A/J and resistant C57BL/6 mice which differ in the degree of susceptibility to clinical malaria following P. chabaudi AS infection. A rapid increase of activated cells (CD25(+), CD44(high), and CD62L(low)) and production of both interferon-gamma and interleukin-4 was found in spleens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…1). Such immune mice exhibited a strong increase in circulating total IgG-antibodies, mainly due to increased levels of IgG2a and IgG2b isotypes (Table 1), which is consistent with previous studies (Langhorne et al 2002;Smith and Taylor-Robinson 2003;Wipasa et al 2009). Remarkably, P. chabaudi-infected erythrocytes, which had disappeared from peripheral blood, were still apparent in liver sections of immune mice before reinfection on day 56 after primary infection (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1). Such immune mice exhibited a strong increase in circulating total IgG-antibodies, mainly due to increased levels of IgG2a and IgG2b isotypes (Table 1), which is consistent with previous studies (Langhorne et al 2002;Smith and Taylor-Robinson 2003;Wipasa et al 2009). Remarkably, P. chabaudi-infected erythrocytes, which had disappeared from peripheral blood, were still apparent in liver sections of immune mice before reinfection on day 56 after primary infection (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Homolog re-infections result only at very low peak parasitemia of approximately 1.5% on day 8 p.i., in contrast to approximately 50% in primary infections. Protective immunity is known to be mediated by antibodies, in particular by IgG2a and IgG2b isotypes, which are dramatically increased in immune mice, in accordance with previous studies (Su and Stevenson 2000;Langhorne et al 2002;Smith and Taylor-Robinson 2003;Wipasa et al 2009). Once again, however, it is conspicuous that we have not detected any changes of those miRNA species which are currently known to be critically involved in adaptive immune responses such as antibody formation, development and maturation of B cells, and formation of memory B cells, CD4 + T cells, and CD8 + T Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Collins et al have reported that reinfection of humans with homologous P. vivax showed a decreased mean daily parasite count and milder fever (Collins et al 2004). It has also been shown that susceptible mice that had been exposed to malaria parasites and drug cured were able to generate protective immunity capable of control parasite growth following reinfection (Wipasa et al 2009). In our monkey malaria model, the animals infected with long-term P. cynomolgi showed lowlevel parasitemia; for these animals, clinical symptoms were terminated before initiation of antimalaria drug treatment, suggesting that a naturally acquired protective immunity was induced by the infection but was insufficient to eliminate the parasite.…”
Section: Discussionmentioning
confidence: 98%